Virtual tour concept: introduction of understanding and conducting in printmaking studio / Mohd Nafis Saad ... [et al.] - Saad, Mohd Nafis; Zakaria, Muhammad Salehuddin; Hashim Amir, Nur Muhammad Amin; Said Ahmad @ Syed Ahmad, Siti Humaini; Merman, Hairulnisak; Razali, Rosmidahanim (2022)
The virtual tour concept is a great way to learn. This idea of touring is used to help students grasp the materials and machinery in the printmaking studio by utilizing virtual concepts to improve teaching and learning. The purpose of this virtual tour concept is a practical process to understand and operate equipment and machines in a printmaking studio for teaching and learning activities. The objectives of this innovation project are to facilitate the teaching and learning process using technology in the department as well as a reference source for lecturers, technical assistants, students, and auditors. The method used is the use of Pano2Vr software in producing an accessible virtual tour. As a result of this innovation, students can get clearer information using this virtual tour concept through the use of technology based on current developments to facilitate the teaching and learning process. This research can provide facilities to all parties such as students, lecturers, and support staff to launch the education process in this modern and sophisticated world.